Cytokine and Immune System Abnormalities in Fibromyalgia and Other Central Sensitivity Syndromes - Staud, Roland (Current Rheumatology Reviews, 2015)
The nervous system as well as the immune system use common signaling molecules for intra- and inter-system communications. Specifically, both entities produce a similar array of peptide and non-peptide transmitters that act on a common set of receptors present in the two systems. One important set of such signaling molecules are cytokines. The wide distribution of cytokine receptors throughout the body, including the immune and the nervous system allows direct communication between these two entities. In addition to cytokines the nervous system and immune system also communicate with each other using shared ligands such as neurotransmitters and neuroendocrine hormones, and their respective receptors. Some of the most important clinical interactions between these two systems are associated with the “sickness response” as well as pain and analgesia. This “sickness response” which has been frequently attributed to inflammatory cytokines, strongly resembles the core symptoms of fibromyalgia and other Central Sensitivity Syndromes (CSS). Therefore a large number of research studies have focused on the relationship between peripheral cytokines and CSS. However, a lack of consistent associations was observed between CSS symptoms and peripheral cytokines which seem to suggest that maybe cytokines abnormalities of the central nervous system contribute to the pathogenesis of these illnesses. Better knowledge of cytokine –nervous system interactions may ultimately benefit the development of interventions that improve CSS manifestations including the “sickness response” and chronic pain.
Keywords: clinical pain